THE CHEMICAL COMPOSITION OF THE EARTH - Allegre C.J.; Poirier J.P.; Humler E.; Hofmann A.W. (My University, 1995)
The bulk composition of the Earth and the composition of the mantle and core are calculated using the ratios of major and trace elements.The ratios of elements which do not enter the core (lithophile) are the same in the bulk Earth as in the mantle. Bulk earth ratios involving an element that does enter the core (siderophile) are therefore determined from meteorite correlation diagrams of siderophile-lithophile ratios vs. lithophile-lithophile ratios and from primitive mantle composition in elements which do not enter the core (e.g., Al). The composition of the core is determined by difference, without resorting to assumption about core formation processes.It is found that the core contains about 7.3 wt% silicon and 2.3 wt% sulphur. To account for the seismologically determined density deficit of the core, about 4 wt% oxygen must be added.The present results are compatible with the idea that the core material equilibrated at low pressure, in reducing conditions. Furthermore, we propose that the Earth is closer to CM rather than to C1 for non-volatile element ratios.